Corticosterone enhances the potency of ethanol against hippocampal long-term potentiation via local neurosteroid synthesis - Izumi, Yukitoshi; O’Dell, Kazuko A.; Zorumski, Charles F. (Frontiers in Cellular Neuroscience, 2015)
Corticosterone is known to accumulate in brain after various stressors including alcohol intoxication. Just as severe alcohol intoxication is typically required to impair memory formation only high concentrations of ethanol (60mM) acutely inhibit long-term potentiation (LTP), a cellular memory mechanism, in naïve hippocampal slices. This LTP inhibition involves synthesis of neurosteroids, including allopregnanolone, and appears to involve a form of cellular stress. In the CA1 region of rat hippocampal slices, we examined whether a lower concentration of ethanol (20 mM) inhibits LTP in the presence of corticosterone, a stress-related modulator, and whether corticosterone stimulates local neurosteroid synthesis. Although low micromolar corticosterone alone did not inhibit LTP induction, we found that 20 mM ethanol inhibited LTP in the presence of corticosterone. At 20 mM, ethanol alone did not stimulate neurosteroid synthesis or inhibit LTP. LTP inhibition by corticosterone plus ethanol was blocked by finasteride, an inhibitor of 5α-reductase, suggesting a role for neurosteroid synthesis. We also found that corticosterone alone enhanced neurosteroid immunostaining in CA1 pyramidal neurons and that this immunostaining was further augmented by 20 mM ethanol. The enhanced neurosteroid staining was blocked by finasteride and the N-methyl-D-aspartate antagonist, 2-amino-5-phosphonovalerate (APV). These results indicate that corticosterone promotes neurosteroid synthesis in hippocampal pyramidal neurons and can participate in ethanol-mediated synaptic dysfunction even at moderate ethanol levels. These effects may contribute to the influence of stress on alcohol-induced cognitive impairment.